Governance of publicly procured island ferry traffic services in the Central Baltic Region - Joki-Korpela, Elias (My University, 2025)
This thesis focuses on the markets, governance models, and public procurement of island ferry services in the Central Baltic Sea Region. Island ferry traffic, referring to publicly provided, procured, or subsidised ferry services in archipelagos and coastal areas, is a highly specific industry in the transport sector. Tourism-based ferry services, road ferries, and large-scale ferry services (as in ferries carrying thousands of passengers per vessel) are excluded from this thesis. Island ferry traffic is a small-scale industry and often creates a difficult business environment, yet it provides a vital service to its end-users. Inhabitants of small islands in the Central Baltic Sea Region are often highly dependent on ferry connections to the mainland and other islands. In the four selected regions of this thesis—Estonia, mainland Finland, Stockholm County in Sweden, and the Åland Islands—these ferry services are publicly procured and governed by various public sector entities. For this thesis, academic literature on market economy, market governance, sustainability in governance, public-private partnerships, and public procurement was studied to form a theoretical foundation. The literature was used to create a spectrum of public-private partnerships, which was used to categorise these partnerships in the island ferry traffic industry. A framework for “good practice and avoidable mistakes” regarding public procurement was also established and used to analyse research results. Data was collected on how the markets function and how authorities approach the governance and public procurement of island ferry services in each of the four regions. The data was collected by interviewing selected experts representing both authorities and service providers. The interview materials were then analysed, and together with secondary sources such as annual reports and relevant online articles, similarities, differences, and defining features of the markets, governance models, and public procurement approaches of island ferry services in the four selected regions were identified. Finally, the research results were evaluated based on key findings from academic literature. The output of this research is a first-of-its-kind study providing insight into the markets, governance models, and public procurement in the highly specific industry of island ferry services in the Central Baltic Region. The research showed that across all four regions public procurement of island ferry services is shifting from a traditional price-focused approach towards emphasising quality and low emissions. It was also found that especially in mainland Finland and the Åland Islands business environments are difficult, while Stockholm County has a relatively stable and competitive market in the island ferry sector. Overall, the island ferry traffic industry is undergoing major changes in the 2020s due to political pressure to achieve emission reductions, new approaches to governance and public procurement, and the increasing need to update vessel technology.